ANALISIS STRATEGI MANAJEMEN FUNDRAISING OLEH LEMBAGA AMIL ZAKAT NURUL HAYAT GRESIK UNTUK MENGOPTIMALKAN DANA ZAKAT, INFAQ, SEDEKAH - Hamidi, Ahmad Iqbal; Ridlwan, Ahmad Ajib (Jurnal Ekonomika dan Bisnis Islam, 2023)
Analyzing the fundraising management strategy applied by Nurul Hayat Gresik Amil Zakat Institution is the goal chosen by the researcher. This research uses descriptive qualitative research with observation, interviews, and documentation. Source triangulation is used to ensure data validity. The results of this study show that the Zakat Infaq Sadaqah (ZIS) fundraising strategy by Nurul Hayat Gresik Amil Zakat Institution is carried out by methods, namely indirect fundraising through social media, banners and pamphlets, direct fundraising through messages or letters and visiting donors directly. In addition, Nurul Hayat Amil Zakat Institution has implemented fundraising management functions well, namely planning, organizing, implementing, and supervising. If the fundraising management strategy has been carried out correctly, the collected zakat, infaq, sadaqah (ZIS) funds will be optimal.